The Impact of Performance Status on Length of Hospital Stay and Clinical Complications Following Liver Transplantation. Issue 9 (September 2021) - Wallace, David; Cowling, Thomas E.; Walker, Kate; Suddle, Abid; Gimson, Alex; Rowe, Ian; Callaghan, Chris; Heaton, Nigel; van der Meulen, Jan; Bernal, William
Abstract : Background: Impaired pretransplant performance status (PS) is associated with chronic liver disease (CLD). We studied its impact on hospital length of stay (LOS), complications, and readmissions in the first year after liver transplantation. Methods: The Standard National Liver Transplant Registry was linked to a hospital administrative dataset, and all first-time liver transplant recipients with CLD aged ≥18 years in England were identified. A modified 3-level Eastern Cooperative Oncology Group score was used to assess PS. Linear- and logistic-fixed effect regression models were used to estimate the effect of specific posttransplant complications and readmissions in the first year after transplantation. Results: Six thousand nine hundred sixty-eight recipients were included. Impaired PS was associated with an increased LOS in the initial posttransplant period (comparing ECOG 1–3, adjusted difference 7.2 d; 95% confidence [CI], 4.8-9.6; P < 0.001) and in time spent on the ITU (adjusted difference 1.2 d; 95% CI, 0.4-2.0; P < 0.001). There was no significant association between ECOG status and total LOS of later admissions (adjusted difference, 2.5 d; 95% CI, –0.4-5.5; P = 0.23). Those with a poorer ECOG status had an increased incidence of renal failure (odds ratio, 1.5; 95% CI, 1.1-2.0; P = 0.004) and infection (odds ratio, 1.2; 95% CI, 1.1-1.4; P = 0.02) but not an increased incidence of readmission (odds ratio, 1.2; 95% CI, 0.9-1.5; P = 0.13). Conclusions: In liver transplant recipients with CLD, impaired pretransplant PS is associated with prolonged LOS in the immediate posttransplant period but not with LOS of later admissions in the first year after transplantation. Impaired PS increased the risk of renal failure and infection. Abstract : Supplemental Digital Content is available in the text.